A dielectric material for MLCC with high-temperature electrical performance stability and a preparation method thereof

CN123017737APending Publication Date: 2026-10-30AI BOTE (HUIZHOU) NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611189044.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]钛酸钡基陶瓷因优异的本征介电性能,是当前MLCC介质材料的主流体系,但其本征居里温度约为120℃,超过居里点后介电常数快速衰减,且高温下易出现晶格氧空位增多、绝缘电阻大幅下降、损耗骤升等问题,难以适配高温工作场景;现有技术中,单一元素晶格掺杂改性仅能有限展宽介电居里峰,但在-55℃~150℃宽温区间内,电容温度变化率仍难以稳定控制在较小范围,高温段介电衰减明显;为提升温稳性的复合改性体系,普遍存在致密化烧结温度偏高的问题,若降低烧结温度则会出现陶瓷致密度不足、气孔缺陷增多、绝缘耐压性能劣化的情况,若引入大量玻璃相辅助烧结又会显著拉低体系室温介电常数,无法同时兼顾高介电常数、宽温介电稳定性、低温致密烧结与优异的高温绝缘可靠性,制约了高温型MLCC的性能提升与规模化低成本应用

Benefits of technology

本发明的一种高温电性能稳定性的MLCC用介质材料及其制备方法,通过将铋钠钛氧化物、锶锆共掺杂钛酸钡、掺杂改性剂以及复合烧结助剂球磨,之后烘干,过筛,之后加入聚乙烯醇水溶液,研磨,过筛,得到造粒粉,称取造粒粉填入不锈钢模具中,压制成生坯片,之后将生坯片放入马弗炉中烧结,冷却,之后送入管式炉恒温区,烧结,保温结束后,降温至室温,得到介质材料;复合烧结助剂可促进介质陶瓷低温致密烧结,细化晶粒并构建高阻晶界以提升绝缘耐压性能,同时调控体系热膨胀、缓解烧结应力,保障瓷体结构与性能稳定;制备方法采用复配粒径氧化锆球湿法球磨,既保证各组分均匀分散,又不破坏玻璃相的非晶结构,完整保留粉体烧结活性,低浓度聚乙烯醇造粒结合阶梯升温排胶,生坯密度均匀,可有效避免鼓泡、开裂与残留气孔缺陷,1230℃空气气氛烧结配合液相助烧,在较低温度下即可实现高致密度,同时抑制晶粒异常长大,工艺重复性好、能耗低;掺杂改性剂为氧化镝、氧化镁、二氧化锰、五氧化二铌按比例复配,可同步实现多重改性效果,稀土镝元素参与晶格调控,进一步优化介电温谱特性,镁、锰元素偏聚于晶界,抑制晶粒长大并构建高阻晶,铌元素发挥电价补偿作用,减少晶格氧空位,降低高温电导损耗,共同提升介质的击穿场强、体积电阻率与高温运行可靠性;锶锆共掺杂钛酸钡作为基体提供高介电基础并通过晶格调控平缓介电常数温度波动,铋钠钛氧化物进一步强化宽温介电稳定性、辅助液相助烧并细化晶粒,二者协同提升介质综合电性能与高温运行可靠性;使介质材料兼具高致密度、高介电常数、低介电损耗、优异绝缘耐压性能与良好宽温介电稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of MLCC dielectric materials, in particular to a MLCC dielectric material with high-temperature electrical performance stability and a preparation method thereof, and aims to solve the technical problems that the existing barium titanate-based MLCC dielectric material has a large capacitance temperature change rate in a wide temperature range, high-temperature dielectric and insulation withstand voltage performance attenuation is significant, and low-temperature dense sintering and high dielectric constant are difficult to be considered; the bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, a doping modifier and a composite sintering aid are ball milled, then dried, screened, then polyvinyl alcohol aqueous solution is added, ground, screened, granulated powder is obtained, the granulated powder is weighed and filled into a stainless steel mold, and a green body sheet is pressed, then the green body sheet is placed into a muffle furnace for sintering, cooled, then sent into a constant temperature zone of a tube furnace for sintering, after the heat preservation is finished, the temperature is lowered to room temperature, and the dielectric material is obtained; the dielectric material has high density, high dielectric constant, low dielectric loss, excellent insulation withstand voltage performance and good wide-temperature dielectric stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of dielectric materials for MLCCs, and specifically to a dielectric material for MLCCs with high-temperature electrical performance stability and its preparation method. Background Technology

[0002] Multilayer ceramic capacitors (MLCCs) are the most widely used and essential passive electronic components in the electronics and information industry, finding applications in consumer electronics, new energy vehicles, industrial measurement and control, aerospace, and oil and gas exploration. As downstream electronic equipment demands higher temperatures and greater reliability, the operating temperature of MLCCs continues to rise. Traditional X7R dielectric materials, with an operating temperature range of only -55℃ to 125℃ and a capacitance change rate of ±15%, can no longer meet these demands. Applications such as new energy vehicle powertrain control systems, downhole exploration equipment, and airborne electronics require MLCCs to operate stably at temperatures of 150℃ and above for extended periods, placing even more stringent requirements on the high-temperature dielectric constant stability, high-temperature dielectric loss, and high-temperature insulation withstand voltage performance of the dielectric materials.

[0003] Barium titanate-based ceramics are the mainstream dielectric material for MLCCs due to their excellent intrinsic dielectric properties. However, their intrinsic Curie temperature is approximately 120°C. Above the Curie point, the dielectric constant decays rapidly, and at high temperatures, problems such as increased lattice oxygen vacancies, a significant decrease in insulation resistance, and a sharp increase in losses easily arise, making them unsuitable for high-temperature operating scenarios. In existing technologies, single-element lattice doping modification can only broaden the dielectric Curie peak to a limited extent. However, within a wide temperature range of -55°C to 150°C, the capacitance temperature change rate is still difficult to stably control within a small range, and dielectric decay is significant at high temperatures. Composite modification systems designed to improve temperature stability generally suffer from excessively high densification sintering temperatures. Lowering the sintering temperature leads to insufficient ceramic density, increased porosity defects, and deterioration of insulation withstand voltage performance. Introducing a large amount of glass phase to assist sintering significantly lowers the room temperature dielectric constant of the system. It is impossible to simultaneously achieve high dielectric constant, wide-temperature dielectric stability, low-temperature densification sintering, and excellent high-temperature insulation reliability, thus restricting the performance improvement and large-scale low-cost application of high-temperature MLCCs.

[0004] Therefore, developing a dielectric material for MLCCs with stable high-temperature electrical properties and its preparation method is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a dielectric material for MLCCs with high-temperature electrical performance stability and its preparation method.

[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a dielectric material for MLCCs with high-temperature electrical performance stability, comprising the following components in parts by weight: The composition includes 20.5-22.5 parts of strontium-zirconium co-doped barium titanate, 1.6-1.8 parts of sodium bismuth titanium oxide, 0.42-0.49 parts of doping modifier, and 0.54-0.60 parts of composite sintering aid; The doping modifier is a mixture of dysprosium oxide, magnesium oxide, manganese dioxide, and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.2. The composite sintering aid is prepared by the following steps: Step b1: Barium carbonate, titanium dioxide, silicon dioxide, and boric acid are manually mixed in an agate mortar for 15-17 minutes. Then, the mixture is placed in a platinum crucible and placed in a muffle furnace. The temperature is increased to 1450℃ at 5℃ / min and held for 2 hours. After that, the mixture is poured into deionized water for rapid cooling and quenching. Glass fragments are collected and placed in a forced-air drying oven. They are dried at 75-80℃ for 4 hours. Then, the mixture is placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol is added, and the solid-liquid mass ratio is 5:6. The mixture is ball-milled at 280-300 r / min for 12-13 hours and dried at 75-80℃ for 8-10 hours. The powder is then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step b2: Mix magnesium oxide, aluminum oxide, silicon dioxide, and boric acid manually in an agate mortar for 15-17 minutes. Then, transfer the mixture to a platinum crucible and place it in a muffle furnace. Heat the mixture to 1480℃ at 5℃ / min and hold for 2 hours. After that, pour the mixture into deionized water for rapid cooling and quenching. Collect the glass fragments and place them in a forced-air drying oven. Dry the glass fragments at 75-80℃ for 4-4.2 hours. Then, place the glass fragments in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Add anhydrous ethanol, with a solid-liquid mass ratio of 5:6. Ball mill the glass for 12-13 hours at 280-300 r / min. Dry the glass for 8-10 hours at 75-80℃. Pass the glass through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step b3: Place barium titanium silicon glass powder, magnesium aluminum silicon glass powder and tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 3-4 hours at a speed of 200-220 r / min, then place in a forced-air drying oven and dry at a temperature of 75-80℃ for 6-7 hours. Pass through a 200-mesh sieve to obtain the composite sintering aid.

[0007] In a preferred embodiment of the present invention, the amounts of barium carbonate, titanium dioxide, silicon dioxide and boric acid in step b1 are 0.28-0.32 mol: 0.18-0.22 mol: 0.38-0.42 mol: 0.09-0.11 mol.

[0008] In a preferred embodiment of the present invention, the amounts of magnesium oxide, aluminum oxide, silicon dioxide and boric acid used in step b2 are 0.20-0.22 mol: 0.18-0.22 mol: 0.48-0.52 mol: 0.07-0.09 mol.

[0009] In a preferred embodiment of the present invention, the amounts of barium titanium silicon glass powder, magnesium aluminum silicon glass powder and tantalum pentoxide used in step b3 are 14-16g: 4-6g: 0.5-0.7g.

[0010] The sodium bismuth titanium oxide is prepared by the following steps: Bismuth oxide, sodium carbonate, and titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used, and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8-8.2 hours at a speed of 280-300 r / min. After that, it was placed in a vacuum drying oven and dried at 75-80℃ for 6-8 hours. Then, it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min. The temperature was held for 3 hours, and then cooled to room temperature with the furnace. The mixture was then removed and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide.

[0011] In a preferred embodiment of the present invention, the amounts of bismuth oxide, sodium carbonate, and titanium dioxide are 1.01-1.02 mol: 1.03-1.05 mol: 4 mol.

[0012] The strontium-zirconium co-doped barium titanate is prepared by the following steps: Barium carbonate, strontium carbonate, titanium dioxide, and zirconium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used, and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8-8.2 hours at a speed of 280-300 r / min. After that, it was placed in a vacuum drying oven and dried at 75-80℃ for 6-8 hours. Then, it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 1080℃ at a heating rate of 5℃ / min. The temperature was held for 4 hours, and then cooled to room temperature with the furnace. The mixture was then removed and passed through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate.

[0013] In a preferred embodiment of the present invention, the ratio of barium carbonate, strontium carbonate, titanium dioxide and zirconium dioxide is 0.085-0.095 mol: 0.008-0.012 mol: 0.082-0.088 mol: 0.012-0.018 mol.

[0014] Secondly, this application provides a method for preparing a dielectric material for MLCCs with high-temperature electrical performance stability, comprising the following steps: Step 1: Weigh out 20.5-22.5 parts by weight of strontium-zirconium co-doped barium titanate, 1.6-1.8 parts of sodium bismuth titanium oxide, 0.42-0.49 parts of doping modifier, and 0.54-0.60 parts of composite sintering aid, and set aside for later use; Step 2: Add sodium bismuth titanium oxide, strontium zirconium co-doped barium titanate, doping modifier, and composite sintering aid to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 12 hours at a speed of 280-300 r / min. Then place it in a vacuum drying oven and dry it at a temperature of 75-80℃ for 8-10 hours. Pass it through a 200-mesh sieve to obtain composite ceramic powder. Step 3: Weigh the composite ceramic powder, add 5% polyvinyl alcohol aqueous solution of the total powder mass, grind and mix in an agate mortar until no agglomeration, pass through an 80-100 mesh sieve to obtain granulated powder, weigh 0.3g of granulated powder into a Φ10mm stainless steel mold, press it into a green sheet at 15MPa pressure for 1min on a powder tablet press, then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, put it in a muffle furnace, first heat to 200℃ at 2℃ / min, hold for 30min, then heat to 600℃ at 2℃ / min, hold for 2h, and let it cool naturally to room temperature with the furnace to obtain the debinding green sheet; Step 4: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230℃ at a heating rate of 5℃ / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5℃ / min to obtain the dielectric material.

[0015] In a preferred embodiment of the present invention, the zirconia balls in step two are grinding balls with a mass ratio of 1:1, consisting of Φ3mm and Φ6mm balls.

[0016] In a preferred embodiment of the present invention, the mass fraction of the polyvinyl alcohol aqueous solution in step three is 10%.

[0017] The beneficial effects of this invention are: This invention discloses a high-temperature electrically stable dielectric material for MLCCs and its preparation method. The method involves ball milling bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, a doping modifier, and a composite sintering aid, followed by drying and sieving. Then, an aqueous solution of polyvinyl alcohol is added, and the mixture is ground and sieved again to obtain granulated powder. The granulated powder is weighed and filled into a stainless steel mold, pressed into green sheets, and then sintered in a muffle furnace. After cooling, the green sheets are transferred to a constant-temperature zone in a tube furnace for sintering. After holding at this temperature, the material is cooled to room temperature to obtain the dielectric material. Materials: Composite sintering aids promote low-temperature dense sintering of dielectric ceramics, refine grains, and construct high-resistivity grain boundaries to improve insulation and withstand voltage performance. Simultaneously, they regulate thermal expansion, alleviate sintering stress, and ensure the stability of the ceramic structure and performance. The preparation method employs wet ball milling of zirconia balls with mixed particle sizes, ensuring uniform dispersion of each component without damaging the amorphous structure of the glass phase and fully preserving the sintering activity of the powder. Low-concentration polyvinyl alcohol granulation combined with step-heating debinding results in uniform green body density, effectively preventing blistering, cracking, and residual porosity. The process employs an air atmosphere sintering method at 1230℃ combined with liquid-phase sintering, achieving high density at a relatively low temperature while suppressing abnormal grain growth. This method offers good process repeatability and low energy consumption. The doping modifiers are a proportional blend of dysprosium oxide, magnesium oxide, manganese dioxide, and niobium pentoxide, simultaneously achieving multiple modification effects. The rare-earth element dysprosium participates in lattice regulation, further optimizing dielectric temperature spectrum characteristics. Magnesium and manganese elements segregate at grain boundaries, inhibiting grain growth and constructing high-resistivity crystals. Niobium element plays a role in valence compensation, reducing lattice oxygen vacancies. By reducing high-temperature conductivity loss, the breakdown field strength, volume resistivity, and high-temperature operational reliability of the dielectric are improved. Strontium-zirconium co-doped barium titanate provides a high dielectric basis as a matrix and smooths the temperature fluctuation of dielectric constant through lattice control. Bismuth sodium titanium oxide further enhances wide-temperature dielectric stability, assists in liquid-phase sintering, and refines grain size. The two work together to improve the overall electrical performance and high-temperature operational reliability of the dielectric. This results in dielectric materials with high density, high dielectric constant, low dielectric loss, excellent insulation withstand voltage performance, and good wide-temperature dielectric stability.

[0018] In the preparation of the dielectric material, a composite sintering aid was first prepared. Firstly, barium carbonate was thermally decomposed into barium oxide and carbon dioxide. Boric acid was gradually dehydrated to generate boron trioxide and water vapor. Subsequently, barium oxide, titanium dioxide, silicon dioxide, and boron trioxide were fully melted at high temperature. Silicon dioxide and boron trioxide formed a continuous amorphous framework using a glass network forging body. Barium oxide and titanium dioxide filled the network gaps as network modifiers. The glass softening temperature and liquid phase viscosity were adjusted. After rapid cooling and water quenching, amorphous glass fragments were obtained, which were then ball-milled into powder, retaining the low-melting-point liquid phase activity of the glass. Boric acid was first thermally dehydrated to generate boron trioxide, which was then oxidized... Magnesium, aluminum oxide, silicon dioxide, and boron trioxide are completely melted at high temperature to form a magnesium aluminum borosilicate glass system. Silicon dioxide serves as the core glass-forming body, constructing the network framework. Boron trioxide lowers the melting temperature of the system. Aluminum oxide partially enters the glass network, enhancing chemical stability and structural strength. Magnesium oxide acts as a modifier, controlling the glass's thermal expansion coefficient and softening point. After water quenching and ball milling, high-insulation glass powder is obtained. The two glass powders are then uniformly mixed with tantalum pentoxide through low-speed, short-time wet ball milling. This low-intensity milling avoids damage to the amorphous structure of the glass and powder agglomeration, ensuring uniform dispersion of tantalum pentoxide. This ensures uniform liquid phase distribution and doping during subsequent sintering. The simultaneous diffusion of impurities provides the foundation; barium titanium silicon glass has a low softening temperature and forms a liquid phase first during sintering. Through mass transfer in the liquid phase, it accelerates particle diffusion and pore filling, achieving low-temperature densification. Magnesium aluminum silicon glass has a moderate viscosity at high temperatures, regulating the overall fluidity of the liquid phase and inhibiting abnormal grain growth. Together, they ensure high density while maintaining uniform grain size. Magnesium aluminum silicon glass itself possesses high insulation and low dielectric loss characteristics. After sintering, it accumulates at grain boundaries to form a continuous high-resistivity grain boundary layer, blocking carrier migration and effectively improving the material's volume resistivity and breakdown field strength. In the system, tantalum pentoxide diffuses with the liquid phase to the grain boundaries and lattice surface, stabilizing lattice oxygen vacancies and reducing high-temperature dielectric loss. This reduces conductivity and further enhances the dielectric insulation reliability and high-temperature load capacity. The two types of glass can synergistically regulate the thermal expansion performance of the system. The barium titanium silicon glass has a similar coefficient of thermal expansion to the barium titanate matrix, ensuring a strong bond between the matrix and the grain boundary phase interface. The low thermal expansion characteristics of the magnesium aluminum silicon glass balance the overall coefficient of thermal expansion, alleviating thermal stress during the sintering cooling stage, reducing sintering defects such as cracking and delamination of the ceramic body, and improving the structural integrity and mechanical strength of the ceramic body after sintering. This composite sintering aid has a stable structure under air sintering and excellent chemical inertness. While improving the densification degree of the ceramic, it fully retains the wide-temperature dielectric properties of the matrix, making it suitable for the application requirements of high-temperature stable MLCC dielectric systems.

[0019] In the preparation of dielectric materials, bismuth sodium titanium oxide and strontium zirconium co-doped barium titanate were prepared. First, the bismuth sodium titanium oxide was prepared using bismuth oxide, sodium carbonate, and titanium dioxide as starting materials. Under high temperature, the components underwent interfacial reactions through particle diffusion, gradually completing phase transformation and ultimately generating perovskite-type bismuth sodium titanium oxide. The reaction was accompanied by the release of carbon dioxide. In the later stages of the reaction, trace amounts of low-melting-point bismuth oxide formed a liquid phase to assist mass transfer, promoting crystal growth and lattice structure improvement. The strontium zirconium co-doped barium titanate was prepared using barium carbonate, strontium carbonate, titanium dioxide, and zirconium dioxide as starting materials. During the reaction, Sr... 2+ Occupying the A site of the perovskite structure, partially replacing Ba 2+ Zr 4+ Occupying part of B position and replacing Ti 4+ Ultimately, a uniform single-phase strontium-zirconium co-doped barium titanate solid solution is formed, simultaneously releasing carbon dioxide. During the high-temperature stage, the dopant elements diffuse fully, forming a structurally complete and compositionally homogeneous perovskite solid solution. As the core matrix of MLCC dielectrics, strontium-zirconium co-doped barium titanate possesses the excellent intrinsic dielectric properties of barium titanate-based perovskites, providing ample basic capacitance output for the device. Furthermore, through the A-site Sr... 2+ Replacement, B-position Zr 4+ The doping lattice modulation effect can lower the Curie temperature and broaden the dielectric response peak, smooth out temperature fluctuations in the dielectric constant, and ensure stable capacitance characteristics over a wide temperature range. Meanwhile, Zr... 4+ Solid solution treatment can stabilize the crystal structure, increase the grain boundary migration barrier, inhibit abnormal grain growth, and form a uniform fine-grained structure, thereby improving grain boundary insulation and breakdown field strength, and reducing dielectric loss. Bismuth sodium titanium oxide, as a composite modifying component, also possesses the wide-temperature dielectric properties of relaxor ferroelectric materials, which can enhance the dielectric relaxation behavior of the system, broaden the dielectric response range, balance the capacitance variation across the entire temperature range, and improve performance consistency under extreme temperature changes. Furthermore, at high temperatures, trace amounts of low-melting-point bismuth-based liquid phase can precipitate, reducing the activation energy of sintering mass transfer, accelerating pore filling, increasing ceramic density, and optimizing microstructure uniformity. To avoid electrode oxidation, element volatilization, and grain coarsening caused by high-temperature sintering, bismuth sodium titanium oxide can segregate at grain boundaries, refine matrix grains, enhance the blocking effect of grain boundaries on charge carriers, further improve dielectric insulation resistance and breakdown voltage, and reduce leakage current and breakdown failure risk; strontium zirconium co-doped barium titanate and bismuth sodium titanium oxide work synergistically, the former provides a high dielectric foundation and structural support with barium titanate matrix as the core, while the latter optimizes dielectric stability across the entire temperature range, assists liquid phase sintering, and improves insulation withstand voltage performance. The two complement each other to achieve a comprehensive improvement in MLCC dielectric capacity, temperature stability, and long-term reliability. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1: This embodiment describes a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: 1.01 mol bismuth oxide, 1.03 mol sodium carbonate and 4 mol titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8 hours at a speed of 280 r / min. After that, it was placed in a vacuum drying oven and dried at 75℃ for 6 hours. Then, it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min. The temperature was held for 3 hours. After cooling to room temperature with the furnace, it was taken out and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide. Step S2: Add 0.085 mol barium carbonate, 0.008 mol strontium carbonate, 0.082 mol titanium dioxide, and 0.012 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8 hours at a speed of 280 r / min. Then place it in a vacuum drying oven and dry it at 75℃ for 6 hours. After that, pass it through a 50-mesh sieve and pour it into an alumina crucible. Place the crucible in a muffle furnace and heat it to 1080℃ at a heating rate of 5℃ / min. Hold it at that temperature for 4 hours. Cool it to room temperature with the furnace and remove it. Pass it through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S3: 0.28 mol barium carbonate, 0.18 mol titanium dioxide, 0.38 mol silicon dioxide, and 0.09 mol boric acid were manually mixed in an agate mortar for 15 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1450℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water for rapid cooling and quenching. Glass fragments were collected and placed in a forced-air drying oven. The glass fragments were dried at 75℃ for 4 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 280 r / min for 12 h and dried at 75℃ for 8 h. The mixture was then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step S4: 0.20 mol magnesium oxide, 0.18 mol aluminum oxide, 0.48 mol silicon dioxide and 0.07 mol boric acid were manually mixed in an agate mortar for 15 min. Then the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1480℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 75℃ for 4 h. Then the mixture was placed in a ball mill jar, using zirconia balls and controlling the ball-to-material mass ratio to be 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 280 r / min for 12 h and dried at 75-80℃ for 8 h. The mixture was then passed through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step S5: Place 14g of barium titanium silicon glass powder, 4g of magnesium aluminum silicon glass powder and 0.5g of tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 3 hours at a speed of 200 r / min, then place in a forced-air drying oven and dry at a temperature of 75℃ for 6 hours. Pass through a 200-mesh sieve to obtain the composite sintering aid. Step S6: Weigh out 20.5 parts by weight of strontium zirconium co-doped barium titanate, 1.6 parts of sodium bismuth titanium oxide, 0.42 parts of doping modifier, and 0.54 parts of composite sintering aid, and set aside for later use; Step S7: Add bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, doping modifier (the doping modifier is dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide compounded in a molar ratio of 1:0.3:0.2:0.2) and composite sintering aid to a polytetrafluoroethylene ball milling jar. Use zirconium oxide balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol, and the solid-liquid mass ratio is 5:6. Ball mill for 12 hours at a speed of 280 r / min. Then place it in a vacuum drying oven and dry it at a temperature of 75℃ for 8 hours. Pass it through a 200-mesh sieve to obtain composite ceramic powder. Step S8: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through an 80-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the green sheet after debinding. Step S9: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0022] Example 2: This embodiment describes a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: 1.015 mol bismuth oxide, 1.04 mol sodium carbonate and 4 mol titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8.1 h at a speed of 290 r / min. After that, it was placed in a vacuum drying oven and dried at 77 °C for 7 h. Then it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900 °C at a heating rate of 5 °C / min. The temperature was held for 3 h. After cooling to room temperature in the furnace, it was taken out and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide. Step S2: Add 0.09 mol barium carbonate, 0.01 mol strontium carbonate, 0.085 mol titanium dioxide, and 0.015 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8.1 h at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at 77 °C for 7 h. After that, pass it through a 50-mesh sieve and pour it into an alumina crucible. Place the crucible in a muffle furnace and heat it to 1080 °C at a heating rate of 5 °C / min. Hold it at that temperature for 4 h. Cool it to room temperature with the furnace and remove it. Pass it through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S3: 0.3 mol barium carbonate, 0.2 mol titanium dioxide, 0.4 mol silicon dioxide, and 0.1 mol boric acid were manually mixed in an agate mortar for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1450℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water for rapid cooling and quenching. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step S4: 0.21 mol magnesium oxide, 0.2 mol aluminum oxide, 0.5 mol silicon dioxide and 0.08 mol boric acid were placed in an agate mortar and manually mixed for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1480℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4.1 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step S5: Place 15g of barium titanium silicon glass powder, 5g of magnesium aluminum silicon glass powder and 0.6g of tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 3.5h at a speed of 210r / min, then place in a forced-air drying oven and dry at a temperature of 77℃ for 6.5h. Pass through a 200-mesh sieve to obtain the composite sintering aid. Step S6: Weigh out 21.5 parts by weight of strontium zirconium co-doped barium titanate, 1.7 parts by weight of sodium bismuth titanium oxide, 0.455 parts by weight of doping modifier and 0.57 parts by weight of composite sintering aid, and set aside. Step S7: Add bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, doping modifier (the doping modifier is dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide compounded in a molar ratio of 1:0.3:0.2:0.2) and composite sintering aid to a polytetrafluoroethylene ball milling jar. Use zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol, and the solid-liquid mass ratio is 5:6. Ball mill for 12 hours at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at a temperature of 77℃ for 9 hours. Pass it through a 200-mesh sieve to obtain composite ceramic powder. Step S8: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 90-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the green sheet after debinding. Step S9: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0023] Example 3: This embodiment describes a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: 1.02 mol bismuth oxide, 1.05 mol sodium carbonate and 4 mol titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8.2 h at a speed of 300 r / min. After that, it was placed in a vacuum drying oven and dried at 80 °C for 8 h. Then it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900 °C at a heating rate of 5 °C / min. The temperature was held for 3 h. After cooling to room temperature in the furnace, it was taken out and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide. Step S2: Add 0.095 mol barium carbonate, 0.012 mol strontium carbonate, 0.088 mol titanium dioxide, and 0.018 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8.2 h at 300 r / min. Then place in a vacuum drying oven and dry at 80 °C for 8 h. After that, pass through a 50-mesh sieve and pour into an alumina crucible. Place the crucible in a muffle furnace and heat to 1080 °C at a heating rate of 5 °C / min. Hold at this temperature for 4 h. Cool to room temperature with the furnace and remove. Pass through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S3: 0.32 mol barium carbonate, 0.22 mol titanium dioxide, 0.42 mol silicon dioxide, and 0.11 mol boric acid were manually mixed in an agate mortar for 17 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1450℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water for rapid cooling and quenching. Glass fragments were collected and placed in a forced-air drying oven and dried at 80℃ for 4 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 300 r / min for 13 h and dried at 80℃ for 10 h. The powder was then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step S4: 0.22 mol magnesium oxide, 0.22 mol aluminum oxide, 0.52 mol silicon dioxide and 0.09 mol boric acid were manually mixed in an agate mortar for 17 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1480℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water for rapid cooling and quenching. Glass fragments were collected and placed in a forced-air drying oven and dried at 80℃ for 4.2 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 300 r / min for 13 h and dried at 80℃ for 10 h. The powder was then passed through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step S5: Place 16g of barium titanium silicon glass powder, 6g of magnesium aluminum silicon glass powder and 0.7g of tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 4 hours at a speed of 220 r / min, then place in a forced-air drying oven and dry at a temperature of 80℃ for 7 hours. Pass through a 200-mesh sieve to obtain the composite sintering aid. Step S6: Weigh out 22.5 parts by weight of strontium zirconium co-doped barium titanate, 1.8 parts of sodium bismuth titanium oxide, 0.49 parts of doping modifier, and 0.60 parts of composite sintering aid, and set aside for later use; Step S7: Add bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, doping modifier (the doping modifier is dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide compounded in a molar ratio of 1:0.3:0.2:0.2) and composite sintering aid to a polytetrafluoroethylene ball milling jar. Use zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol, and the solid-liquid mass ratio is 5:6. Ball mill for 12 hours at a speed of 300 r / min. Then place it in a vacuum drying oven and dry it at a temperature of 80℃ for 10 hours. Pass it through a 200-mesh sieve to obtain composite ceramic powder. Step S8: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 100-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the green sheet after debinding. Step S9: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0024] Comparative Example 1: This comparative example illustrates a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: Add 0.09 mol barium carbonate, 0.01 mol strontium carbonate, 0.085 mol titanium dioxide, and 0.015 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8.1 h at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at 77 °C for 7 h. After that, pass it through a 50-mesh sieve and pour it into an alumina crucible. Place the crucible in a muffle furnace and heat it to 1080 °C at a heating rate of 5 °C / min. Hold it at that temperature for 4 h. Cool it to room temperature with the furnace and remove it. Pass it through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S2: 0.3 mol barium carbonate, 0.2 mol titanium dioxide, 0.4 mol silicon dioxide, and 0.1 mol boric acid were manually mixed in an agate mortar for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1450℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step S3: 0.21 mol magnesium oxide, 0.2 mol aluminum oxide, 0.5 mol silicon dioxide and 0.08 mol boric acid were manually mixed in an agate mortar for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1480℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4.1 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step S4: Place 15g of barium titanium silicon glass powder, 5g of magnesium aluminum silicon glass powder, and 0.6g of tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 3.5h at a speed of 210r / min, then place in a forced-air drying oven and dry at a temperature of 77℃ for 6.5h. Pass through a 200-mesh sieve to obtain the composite sintering aid. Step S5: Weigh out 21.5 parts by weight of strontium-zirconium co-doped barium titanate, 0.455 parts by weight of doping modifier and 0.57 parts by weight of composite sintering aid, and set aside; Step S6: Strontium-zirconium co-doped barium titanate, doping modifier (the doping modifier is a compound of dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.2) and composite sintering aid are added to a polytetrafluoroethylene ball mill jar. Zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) are used and the ball-to-material mass ratio is controlled at 4:1. Anhydrous ethanol is added, and the solid-liquid mass ratio is 5:6. The mixture is ball-milled for 12 hours at a speed of 290 r / min. Then it is placed in a vacuum drying oven and dried at a temperature of 77℃ for 9 hours. The powder is then passed through a 200-mesh sieve to obtain composite ceramic powder. Step S7: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 90-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the debinding green sheet. Step S8: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0025] Comparative Example 2: This comparative example illustrates a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: 1.015 mol bismuth oxide, 1.04 mol sodium carbonate and 4 mol titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8.1 h at a speed of 290 r / min. After that, it was placed in a vacuum drying oven and dried at 77 °C for 7 h. Then it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900 °C at a heating rate of 5 °C / min. The temperature was held for 3 h. After cooling to room temperature in the furnace, it was taken out and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide. Step S2: Add 0.09 mol barium carbonate, 0.01 mol strontium carbonate, 0.085 mol titanium dioxide, and 0.015 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8.1 h at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at 77 °C for 7 h. After that, pass it through a 50-mesh sieve and pour it into an alumina crucible. Place the crucible in a muffle furnace and heat it to 1080 °C at a heating rate of 5 °C / min. Hold it at that temperature for 4 h. Cool it to room temperature with the furnace and remove it. Pass it through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S3: Weigh out 21.5 parts by weight of strontium zirconium co-doped barium titanate, 1.7 parts by weight of sodium bismuth titanium oxide and 0.455 parts by weight of doping modifier, and set aside. Step S4: Bismuth sodium titanium oxide, strontium zirconium co-doped barium titanate, and doping modifier (the doping modifier is a mixture of dysprosium oxide, magnesium oxide, manganese dioxide, and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.2) are added to a polytetrafluoroethylene ball milling jar. Zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls in a mass ratio of 1:1) are used, and the ball-to-material mass ratio is controlled at 4:1. Anhydrous ethanol is added, and the solid-liquid mass ratio is 5:6. The mixture is ball-milled for 12 hours at a speed of 290 r / min. After that, it is placed in a vacuum drying oven and dried at a temperature of 77℃ for 9 hours. The powder is then passed through a 200-mesh sieve to obtain composite ceramic powder. Step S5: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 90-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the debinding green sheet. Step S6: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0026] Comparative Example 3: This comparative example illustrates a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: Add 0.09 mol barium carbonate, 0.01 mol strontium carbonate, 0.085 mol titanium dioxide, and 0.015 mol zirconium dioxide to a polytetrafluoroethylene ball mill jar. Use zirconium oxide balls and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol to make the solid-liquid mass ratio 5:6. Ball mill for 8.1 h at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at 77 °C for 7 h. After that, pass it through a 50-mesh sieve and pour it into an alumina crucible. Place the crucible in a muffle furnace and heat it to 1080 °C at a heating rate of 5 °C / min. Hold it at that temperature for 4 h. Cool it to room temperature with the furnace and remove it. Pass it through a 50-mesh sieve to obtain strontium-zirconium co-doped barium titanate. Step S2: Weigh out 21.5 parts by weight of strontium zirconium co-doped barium titanate and 0.455 parts by weight of doping modifier, and set aside; Step S3: Strontium-zirconium co-doped barium titanate and doping modifier (the doping modifier is a mixture of dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.2) are added to a polytetrafluoroethylene ball milling jar. Zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) are used and the ball-to-material mass ratio is controlled at 4:1. Anhydrous ethanol is added, and the solid-liquid mass ratio is 5:6. The mixture is ball-milled for 12 hours at a speed of 290 r / min. After that, it is placed in a vacuum drying oven and dried at a temperature of 77℃ for 9 hours. The powder is then passed through a 200-mesh sieve to obtain composite ceramic powder. Step S4: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 90-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the green sheet after debinding. Step S5: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0027] Comparative Example 4: This comparative example illustrates a method for preparing a dielectric material for MLCCs with stable high-temperature electrical properties, comprising the following steps: Step S1: 1.015 mol bismuth oxide, 1.04 mol sodium carbonate and 4 mol titanium dioxide were added to a polytetrafluoroethylene ball mill jar. Zirconia balls were used and the ball-to-material mass ratio was controlled at 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled for 8.1 h at a speed of 290 r / min. After that, it was placed in a vacuum drying oven and dried at 77 °C for 7 h. Then it was passed through a 50-mesh sieve and poured into an alumina crucible. The crucible was placed in a muffle furnace and heated to 900 °C at a heating rate of 5 °C / min. The temperature was held for 3 h. After cooling to room temperature in the furnace, it was taken out and passed through a 50-mesh sieve to obtain sodium bismuth titanium oxide. Step S2: 0.3 mol barium carbonate, 0.2 mol titanium dioxide, 0.4 mol silicon dioxide, and 0.1 mol boric acid were manually mixed in an agate mortar for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1450℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain barium titanium silicon glass powder. Step S3: 0.21 mol magnesium oxide, 0.2 mol aluminum oxide, 0.5 mol silicon dioxide and 0.08 mol boric acid were manually mixed in an agate mortar for 16 min. Then, the mixture was placed in a platinum crucible and placed in a muffle furnace. The temperature was increased to 1480℃ at 5℃ / min and held for 2 h. After that, the mixture was poured into deionized water and quenched quickly. Glass fragments were collected and placed in a forced-air drying oven and dried at 77℃ for 4.1 h. Then, the mixture was placed in a ball mill jar, using zirconia balls with a ball-to-material mass ratio of 4:1. Anhydrous ethanol was added, and the solid-liquid mass ratio was 5:6. The mixture was ball-milled at 290 r / min for 12.5 h and dried at 77℃ for 9 h. The powder was then passed through a 200-mesh sieve to obtain magnesium aluminum silicon glass powder. Step S4: Place 15g of barium titanium silicon glass powder, 5g of magnesium aluminum silicon glass powder, and 0.6g of tantalum pentoxide into a ball mill jar, use zirconia balls and control the ball-to-material mass ratio to be 3:1, add anhydrous ethanol, and the solid-liquid mass ratio to be 5:6. Ball mill for 3.5h at a speed of 210r / min, then place in a forced-air drying oven and dry at a temperature of 77℃ for 6.5h. Pass through a 200-mesh sieve to obtain the composite sintering aid. Step S5: Weigh out 21.5 parts by weight of strontium zirconium co-doped barium titanate, 1.7 parts by weight of sodium bismuth titanium oxide, 0.455 parts by weight of doping modifier and 0.57 parts by weight of composite sintering aid, and set aside. Step S6: Add sodium bismuth titanium oxide, barium titanate, doping modifier (the doping modifier is a compound of dysprosium oxide, magnesium oxide, manganese dioxide and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.2) and composite sintering aid to a polytetrafluoroethylene ball milling jar. Use zirconia balls (zirconia balls are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1) and control the ball-to-material mass ratio to be 4:1. Add anhydrous ethanol, and the solid-liquid mass ratio is 5:6. Ball mill for 12 hours at a speed of 290 r / min. Then place it in a vacuum drying oven and dry it at a temperature of 77℃ for 9 hours. Pass it through a 200-mesh sieve to obtain composite ceramic powder. Step S7: Weigh the composite ceramic powder and add 5% of the total mass of the powder to a polyvinyl alcohol aqueous solution (the mass fraction of the polyvinyl alcohol aqueous solution is 10%). Grind and mix in an agate mortar until there is no agglomeration. Pass through a 90-mesh sieve to obtain granulated powder. Weigh 0.3g of granulated powder and fill it into a Φ10mm stainless steel mold. Press it into a green sheet (10mm in diameter and 1mm in thickness) at 15MPa pressure for 1min on a powder press. Then place the green sheet flat in an alumina crucible, spread a layer of alumina embedding powder to prevent adhesion, and put it into a muffle furnace. First, heat it to 200℃ at 2℃ / min and hold it for 30min. Then, heat it to 600℃ at 2℃ / min and hold it for 2h. Let it cool naturally to room temperature with the furnace to obtain the debinding green sheet. Step S8: Place the debinding green blank into an alumina boat and send it into the constant temperature zone of a tube furnace for air sintering. Heat the blank to 1230°C at a heating rate of 5°C / min and hold for 2 hours. After holding, cool the blank to room temperature at a cooling rate of 5°C / min to obtain the dielectric material.

[0028] Performance testing The dielectric materials of Examples 1-3 and Comparative Examples 1-4 were tested according to the following methods; Relative density test: The Archimedes water displacement method was used for the test. The sintered ceramic sample was placed in a forced-air drying oven and dried at 105℃ for 2 hours to remove surface adsorbed moisture. After being taken out, it was placed in a desiccator to cool to room temperature. The dry weight of the sample and the suspended weight immersed in deionized water were weighed separately. The actual density of the sample was calculated according to the Archimedes principle. The ratio of the actual density to the theoretical density was calculated based on the theoretical density of the corresponding matrix. Three parallel samples were tested for each group of samples, and the average value of the results was taken.

[0029] Room temperature dielectric constant test: A precision LCR digital bridge was used for testing. Before the test, silver paste was uniformly coated on both sides of the ceramic sample. The sample was placed in a muffle furnace and heated to 600℃ at a rate of 5℃ / min and held for 10min to form a silver electrode. Under the conditions of room temperature 25℃ and relative humidity 40%, the test frequency was set to 1kHz and the AC test voltage was 1V. The capacitance value of the sample was read, and the thickness was measured at 5 points (center and edge) of the sample. The average value was taken. Combined with the effective area of ​​the electrode, the room temperature relative dielectric constant was calculated using the dielectric constant formula of a parallel plate capacitor. Five parallel samples were tested for each group of samples, and the average value of the results was taken.

[0030] Dielectric loss test: The dielectric constant at room temperature is tested synchronously with the dielectric constant at room temperature of 25℃, test frequency of 1kHz and AC voltage of 1V. The dielectric loss tangent (tanδ) is directly read by LCR digital bridge. Five parallel samples are tested for each group of samples. After removing outliers, the arithmetic mean is taken as the final result.

[0031] Breakdown field strength test: The test was conducted using a voltage breakdown tester. The ceramic sample with double-sided silver-infiltrated electrodes was completely immersed in room temperature insulating silicone oil to prevent surface flashover during the test. A DC uniform voltage boost mode was used, with the boost rate set to 1kV / s. The voltage was continuously applied until the sample broke down, and the voltage value at the moment of breakdown was recorded. After breakdown, the sample thickness at the breakdown point was measured. The breakdown voltage was divided by the corresponding thickness to obtain the breakdown field strength of a single sample. Ten parallel samples were tested for each group of samples, and the arithmetic mean of the results was taken.

[0032] Volume resistivity test: A high resistance meter (insulation resistance tester) was used for the test. Before the test, silver electrodes were prepared on both sides of the sample. A DC test voltage of 100V was applied at room temperature and charged for 60s. After the value stabilized, the insulation resistance value of the sample was read. The volume resistivity of the sample was calculated by combining the electrode area and thickness of the sample with the volume resistivity calculation formula. Five parallel samples were tested for each group of samples, and the average value of the results was taken.

[0033] Capacitance temperature change rate test: A high and low temperature alternating test chamber with a precision LCR digital bridge was used for testing. The capacitance value measured at 25℃ was used as the baseline value. Test temperature points were set within the temperature range of -55℃ to 150℃: -55℃, -40℃, -25℃, 0℃, 25℃, 50℃, 85℃, 100℃, 125℃, and 150℃. The heating and cooling rate was controlled at 5℃ / min. After reaching each target temperature point, the temperature was held constant for 30 minutes to ensure uniform and stable internal temperature of the sample. Subsequently, the capacitance value at that temperature point was read under test conditions of 1kHz and 1V, and calculated according to the formula ΔC / C. 25 =(C T -C 25 ) / C 25 Calculate the capacitance change rate at each temperature point by multiplying by 100%, and take the maximum absolute value of the change in both positive and negative directions as the capacitance temperature change rate for the entire temperature range.

[0034] The test results are shown in Table 1: Table 1: Test Results Summary Table Referring to Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the dielectric material prepared by the present invention has high density, high dielectric constant, low dielectric loss, excellent insulation withstand voltage performance and good wide-temperature dielectric stability.

[0035] Based on the comparison between Example 2 and Comparative Example 1, it can be seen that after removing sodium bismuth titanium oxide from Comparative Example 1, the dielectric constant of the material at room temperature decreases, the dielectric constant attenuates severely in the high-temperature range, the capacitance temperature variability increases significantly, and the high-temperature dielectric stability deteriorates significantly. This proves that sodium bismuth titanium oxide can effectively mitigate high-temperature dielectric decay and narrow the fluctuation range of capacitance with temperature, making it a key component for ensuring the stability of dielectric performance over a wide temperature range and at high temperatures.

[0036] Based on the comparison between Example 2 and Comparative Example 2, it can be seen that Comparative Example 2, without the addition of composite sintering aid, resulted in a significant decrease in ceramic sintering density, an increase in dielectric loss, and a substantial decrease in breakdown field strength and volume resistivity. This indicates that the composite sintering aid can form a liquid phase to promote sintering densification, while simultaneously constructing a high-resistivity insulating layer at the grain boundaries, thereby refining the grains, reducing leakage current, and improving withstand voltage insulation performance.

[0037] Based on the comparison between Example 2 and Comparative Example 3, it can be seen that after removing both sodium bismuth titanium oxide and the composite sintering aid in Comparative Example 3, the ceramic density, dielectric constant, breakdown field strength, and volume resistivity were the lowest among all groups, while the capacitance temperature change rate reached the maximum value. It can be inferred that the ceramic is prone to abnormal grain growth and an increase in micropores and microcracks. The performance degradation caused by the absence of both is superimposed, which fully demonstrates that sodium bismuth titanium oxide and the composite sintering aid have a significant synergistic effect. The combination of the two can take into account both dense sintering and wide-temperature dielectric stability.

[0038] Based on the comparison between Example 2 and Comparative Example 4, it can be seen that although the room temperature dielectric constant of Comparative Example 4 increased significantly after replacing the strontium-zirconium co-doped barium titanate with undoped pure barium titanate, the capacitance temperature variation rate deteriorated sharply, and the breakdown field strength and volume resistivity decreased significantly. This proves that Sr and Zr co-doping can regulate the barium titanate crystal lattice, disperse the sharp ferroelectric-paraelectric phase transition, effectively compress the capacitance temperature variation range, and improve the wide-temperature and high-temperature dielectric stability of the material. It is an indispensable basic modification method for this dielectric system.

[0039] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0040] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.

Claims

1. A dielectric material for MLCCs with high-temperature electrical performance stability, characterized in that, Includes the following components by weight: The composition includes 20.5-22.5 parts of strontium-zirconium co-doped barium titanate, 1.6-1.8 parts of sodium bismuth titanium oxide, 0.42-0.49 parts of doping modifier, and 0.54-0.60 parts of composite sintering aid; The doping modifier is a mixture of dysprosium oxide, magnesium oxide, manganese dioxide, and niobium pentoxide in a molar ratio of 1:0.3:0.2:0.

2. The composite sintering aid is prepared by the following steps: Step b1: Mix barium carbonate, titanium dioxide, silicon dioxide and boric acid, then sinter, quench in water after rapid cooling, dry, then ball mill, dry, and sieve to obtain barium titanium silicon glass powder; Step b2: Mix magnesium oxide, aluminum oxide, silicon dioxide and boric acid, then sinter, quench in water after rapid cooling, dry, ball mill, dry, and sieve to obtain magnesium aluminum silicon glass powder; Step b3: Barium titanium silicon glass powder, magnesium aluminum silicon glass powder and tantalum pentoxide are ball-milled, then dried and sieved to obtain composite sintering aid.

2. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The amounts of barium carbonate, titanium dioxide, silicon dioxide, and boric acid used in step b1 are 0.28-0.32 mol: 0.18-0.22 mol: 0.38-0.42 mol: 0.09-0.11 mol.

3. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, In step b2, the amounts of magnesium oxide, aluminum oxide, silicon dioxide, and boric acid are 0.20-0.22 mol: 0.18-0.22 mol: 0.48-0.52 mol: 0.07-0.09 mol.

4. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The amounts of barium titanium silicon glass powder, magnesium aluminum silicon glass powder, and tantalum pentoxide used in step b3 are 14-16g: 4-6g: 0.5-0.7g.

5. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The sodium bismuth titanium oxide is prepared by the following steps: Bismuth oxide, sodium carbonate, and titanium dioxide were ball-milled, then dried, sieved, sintered, cooled, and sieved again to obtain sodium bismuth titanium oxide.

6. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The amounts of bismuth oxide, sodium carbonate, and titanium dioxide are 1.01-1.02 mol: 1.03-1.05 mol: 4 mol.

7. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The strontium-zirconium co-doped barium titanate is prepared by the following steps: Barium carbonate, strontium carbonate, titanium dioxide, and zirconium dioxide were ball-milled, then dried, sieved, sintered, cooled, and sieved again to obtain strontium-zirconium co-doped barium titanate.

8. The dielectric material for MLCCs with high-temperature electrical performance stability according to claim 1, characterized in that, The ratio of barium carbonate, strontium carbonate, titanium dioxide, and zirconium dioxide is 0.085-0.095 mol: 0.008-0.012 mol: 0.082-0.088 mol: 0.012-0.018 mol.

9. A method for preparing a dielectric material for MLCCs with high-temperature electrical performance stability, characterized in that, The method for preparing a dielectric material for MLCCs with high-temperature electrical performance stability as described in any one of claims 1-8 comprises the following steps: Step 1: Weigh out 20.5-22.5 parts by weight of strontium-zirconium co-doped barium titanate, 1.6-1.8 parts of sodium bismuth titanium oxide, 0.42-0.49 parts of doping modifier, and 0.54-0.60 parts of composite sintering aid, and set aside for later use; Step 2: Ball mill the sodium bismuth titanium oxide, strontium zirconium co-doped barium titanate, doping modifier, and composite sintering aid, then dry and sieve to obtain composite ceramic powder; Step 3: Weigh the composite ceramic powder, add polyvinyl alcohol aqueous solution, grind, sieve to obtain granulated powder, weigh the granulated powder and fill it into a stainless steel mold, press it into green sheet, then sinter the green sheet and cool it to obtain the debinding green sheet; Step 4: Place the debinding green body into an alumina boat, sinter, and after heat preservation, cool it to room temperature to obtain the dielectric material.

10. The method for preparing a high-temperature electrical performance stable dielectric material for MLCCs according to claim 9, characterized in that, The zirconia balls used in step two are Φ3mm and Φ6mm grinding balls with a mass ratio of 1:1; the polyvinyl alcohol aqueous solution used in step three has a mass fraction of 10%.